DIFERENSIASI KONTRAK STANDAR DIKAITKAN DENGAN PENERAPAN PRINSIP UNIDROIT - Bambang Herlambang Irawan Nurraid (2023)
The world is increasingly showing its development both in terms of culture and legal adaptations that increasingly bring this International Business environment to be newer and more modern. This change is based on legal events that occur, one of which is the existence of legal problems in conducting Cooperation agreements on an international scale such as the example of a loan agreement to PT Bangun Karya Pratama Lestari (BKPL) by NINE AM Ltd which is hampered by the process of paying debts and obstacles in filing a lawsuit. This is certainly a problem because the agreement written by NINE AM Ltd does not use Indonesian as the country of choice of law and must collide with Law No. 24 of 2009 concerning Flags, Languages, and State Emblems, as well as National Songs. The UNIDROIT principle is the answer to the problem where it contains the principle of freedom of contract that can encourage parties to be able to give clauses or choose this principle as a choice of law. Because the use of unidroit as a choice of law can really harmonize the relationship between parties and avoid problems that clash with the positive law that applies in Indonesia. So for any country that has ratified this principle should certainly prioritize ease and flexibility in drafting agreements, a complicated and convoluted process raises the attitude of relationships that are less worthy of being seen let alone can affect the development of business at large with various countries.